2019
DOI: 10.1039/c9sc01422e
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent interchromophoric interaction in a fluorescent pyrene-based metal–organic framework

Abstract: Variable temperature experiments revealed that the fluorescent emission colour of the pyrene-based SION-7 changes from blue at 80 K to yellow-green at 450 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 70 publications
4
40
0
Order By: Relevance
“…The intensity of excimer peak at 539 nm was quenched with an increase in temperature from 30 to 100 C. At 100 C, the excimer peak (at 539 nm) was blue-shifted and it's intensity reduced 25 1.6 times than that of at 30 C (ESI, Figure S7). However, controlled cooling leads to almost retention of fluorescent intensity and peak position.…”
Section: Resultsmentioning
confidence: 98%
“…The intensity of excimer peak at 539 nm was quenched with an increase in temperature from 30 to 100 C. At 100 C, the excimer peak (at 539 nm) was blue-shifted and it's intensity reduced 25 1.6 times than that of at 30 C (ESI, Figure S7). However, controlled cooling leads to almost retention of fluorescent intensity and peak position.…”
Section: Resultsmentioning
confidence: 98%
“…Materials exhibiting tunable fluorescence emission upon heating or cooling are considered smart materials as their optical properties can be exquisitely controlled by adjusting the external temperature. 83 It is known that the pyrene-based MOF topology plays an important role in the interchromophoric interactions behavior of the excited stated, 169 yet the temperature is also an important factor. Gładysiak et al 83 reported a pyrene-based MOF, SION-7, which can display either monomer or excimer fluorescence emission due to the temperature-dependent extent of interchromophoric interactions between the TBAPy 3ligands within the framework.…”
Section: Luminescence Sensingmentioning
confidence: 99%
“…83 It is known that the pyrene-based MOF topology plays an important role in the interchromophoric interactions behavior of the excited stated, 169 yet the temperature is also an important factor. Gładysiak et al 83 reported a pyrene-based MOF, SION-7, which can display either monomer or excimer fluorescence emission due to the temperature-dependent extent of interchromophoric interactions between the TBAPy 3ligands within the framework. The same phenomena has been also reported in Cd, Co, and Zn TBAPy-based MOFs where the temperature is a key parameter in the interchromophoric interactions.…”
Section: Luminescence Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The cadmium(II) ion with full‐occupied 4d orbits was selected for its absence of the d‐d transition. 1,3,6,8‐Tetrakis(4‐carboxylphenyl)pyrene with a π‐conjugated aromatic pyrene core is attractive fluorescent molecule due to its use as optical brighteners, dyes, or dye precursor , . A novel compound with the formula of {[Cd(TBAPy)(H 2 O) 2 ] · 4(H 2 O)} n ( 1 ) is presented herein.…”
Section: Introductionmentioning
confidence: 99%